Effect of Parenting on Stunting Incidence in Infant Aged 0-59 Months Old - Andi Surahman Batara; Idhar Darlis (Journal of Public Health and Pharmacy)
Introduction: Parenting is a factor most significantly affect and contribute to the incidence of stunting in infants aged 0-59 months. Parenting has recently attracted many attentions since parents are the one who have the most interaction with their own children. Hence, current research was carried out to know the correlation between parenting and the incidence of stunting in infants aged 0-59 months.